Stimulation of the manufacturing industry in the Republic of Kazakhstan - Tasbulatova, D.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the issues of the strategic development of the manufacturing industry in the Republic of Kazakhstan are considered, as well as separate programs with the implementation of their own plan of goals and objectives, offering methods and measures for state support for each of the most important branches of the manufacturing industry. The relationship of industry with other economic categories, providing a basic analysis of support programs offered annually in the Messages of the President of the Republic of Kazakhstan. The main problem of studying issues related to the manufacturing industry is explained by the fact that through reproduction new technologies are always created, which often contribute to the growth of other sectors of the economy. New strategies of the manufacturing industry will increase the export of manufactured domestic products, which means the growth of exports in the manufacturing industry. The paper studies the problem of analyzing the trends in the development of the manufacturing industry segment, identifies the growth factors of the engineering industries, determining innovative and technological development and ensuring the transition to a new level of industrial production. The structure of the pre-industrial cycle is considered, trends in innovation growth and an adequate development strategy are analyzed. The analysis of programs of state support of industrial production is given, taking into account the factors of the form of the organization and the type of strategy of innovation and technological development.